Development of depression symptoms model for thyroid disorders patients in malaysia - Jaafar, Siti Nur Illiani; Saidi, Sanisah; Daud, Azlina; Musa, Ramli; Nik Ahmad, Nik Nur Fatnoon (2019)
Thyroid disorder patients have a high chance of experiencing depression, resulting from thyroid hormone fluctuations. The objectives of the study were to determine the prevalence of depression and its associated factors among thyroid disorder patients. 846 thyroid disorder patients were recruited from four selected government hospitals in Malaysia. Data were collected by using three questionnaires, including the Depression Anxiety Stress Scale-Depression (DASS-D), the List of Threatening Experiences (LTE) and the Multidimensional Scale of Perceived Social Support (MSPSS). The findings of this study showed that 13.9% (n = 118/846) had mild to extremely severe depression; and more commonly among hypothyroid patient. Meanwhile, young adult (p = 0.001), high TSH (p = 0.05), stressful life events (p = 0.01) and low perceived social support (p = 0.01) were found to have significant association with depression. The model of factors associated with depression among thyroid disorder patients was fitted with Modified Depression Anxiety Stress Scale-Depression (MDASS-D) demonstrated good fit in CFA with adequate divergent and convergent validity and good factor loading (0.62-0.83). The MDASS-D also displayed excellent internal consistency with Cronbach’s alpha of 0.91. The findings of the current study could be useful as baseline data and for providing basic information for developing suitable programmes to prevent depression and improve quality of life among thyroid disorder patients.